Humanity in the signs of Ahmed Mater. - Dr. Abdul Karim Khudair Al-Saadi. (Journal of College of Education, 2024)
This critical paper sought to identify the presence of humanization in Ahmed Matar’s poetry, and by humanization here we mean granting human qualities to non-humans. The researcher reached several results, including that Ahmed Matar was able to employ humanization for the purpose of sending ideological messages represented by his criticism of his miserable political and social reality, and he was able to The poet, through his distribution of human attributes to beings with a soul such as animals, to inanimate objects, to spiritual beings, and to natural beings such as the moon, the sun, the sea, and others, made some of those beings speak to humans, act like them, and even think like them, all so that he could send his messages that He flogs himself and his people there